2011
DOI: 10.1016/j.scr.2010.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Sox2 expression effects on direct reprogramming efficiency as determined by alternative somatic cell fate

Abstract: Induced pluripotent stem cells (iPSCs) are generated by directly reprogramming somatic cells by forcing them to express the exogenous transcription factors, Oct4, Sox2, Klf4 and c-Myc (OSKM). These cells could potentially be used in clinical applications and basic research. Here, we explored the molecular role of Sox2 by generating iPSCs that expressed Sox2 at various levels. Low Sox2 (LS) expression increased the efficiency of generating partially reprogrammed iPSCs in combination with OKM. Notably, we detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 43 publications
6
40
0
2
Order By: Relevance
“…Generally, overexpression of Sox2 is required unless the somatic cells already have endogenous Sox2 expression (Hanna et al, 2010;Stadtfeld and Hochedlinger, 2010). Moreover, the level of SOX2 expression has a direct effect on the rate of direct reprogramming of somatic cells to iPSCs (Yamaguchi et al, 2011). These results provide further support for the assumption that SOX2 has a definitive role in the maintenance of ESCs.…”
Section: Introductionmentioning
confidence: 58%
“…Generally, overexpression of Sox2 is required unless the somatic cells already have endogenous Sox2 expression (Hanna et al, 2010;Stadtfeld and Hochedlinger, 2010). Moreover, the level of SOX2 expression has a direct effect on the rate of direct reprogramming of somatic cells to iPSCs (Yamaguchi et al, 2011). These results provide further support for the assumption that SOX2 has a definitive role in the maintenance of ESCs.…”
Section: Introductionmentioning
confidence: 58%
“…The use of factor combinations to induce lineage conversion raises an important question: do different expression levels of different exogenous factors affect the outcome of lineage reprogramming? Results from the mechanistic analysis of iPSC reprogramming have provided evidence that factor stoichiometry not only influences the reprogramming process but also the quality of iPSCs (Carey et al, 2011;Papapetrou et al, 2009;Tiemann et al, 2011;Yamaguchi et al, 2011). For example, high levels of exogenous Oct4 and Klf4 protein combined with low levels of Sox2 and c-Myc resulted in the generation of high-quality iPSCs with the ability of generating mice through tetraploid complementation (Carey et al, 2011).…”
Section: Exploration Of the Molecular Mechanisms Of Lineage Reprogrammentioning
confidence: 99%
“…For example, iPSC-derived secondary fibroblasts carrying doxycycline-inducible OSKM expression cassettes, which achieve a uniform expression of OSKM at levels required for iPSC generation, can be efficiently reprogrammed to pluripotency (Wernig et al, 2008). Additionally, it has been observed that reprogramming efficiency is enhanced by increasing levels of OCT3/4 and KLF4 (Papapetrou et al, 2009;Tiemann et al, 2011) as well as by lowering SOX2 expression (Yamaguchi et al, 2010). It has also been shown that in the early phase of reprogramming towards pluripotency, OCT3/4 and SOX2 promote the expression of mesendodermal and neuroectodermal genes, respectively (Shu et al, 2013), whereas KLF4 can induce the expression of epidermal genes in a context-dependent manner (Kim et al, 2015).…”
Section: Several Routes To Pluripotency: Mechanisms Of Cell Reprogrammentioning
confidence: 99%